An Agrophysiological study of green beans given atonik and N, P, K fertilizers - Hasfiah Hasfiah; Adriati Adriati (JURNAL AGRIYAN: JURNAL AGROTEKNOLOGI UNIDAYAN, 2019)
Atonic and N, P, K fertilizer have great potential to increase the growth and production of green beans. This study aims to determine atonic and N, P, K fertilizer and their interaction with growth and production of green bean plants. This research was conducted in august 2018 to october 2018 in the Village Of Wakalambe, Kapontori District Buton District Southeast Sulawesi. The study applied a randomized block design (RBD) factorial pattern with two treatments namely atonic (1 ml/10 L water, 2 ml/10 L air, 3 ml/10 L water) and fertilizer N,P,K 200 kg ha-1 N + 100 kg ha-1 P + 75 kg ha-1 K , 250kg ha-1 N + 150 kg ha-1 P + 100 kg ha-1 K, 300kg ha-1 N + 200kg ha-1 P + 125 kgha-1), which is grouped into three groups. The research response design included the number of leaves, the width of leaf, number of pods, the number of grains, dry grain weight, net assimilation rate, relative growth rate, root loss ratio and ton ha-1 production.